Pengaruh Self Efficacy Dalam Upaya Meningkatkan Kemandirian Usaha UKM Di Kecamatan Percut Sei Tuan - Nel Arianty; Julita Julita; Rahmad Bahagia (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2020)
Apart from being a source of personal income, entrepreneurship can also open up jobs which will certainly contribute to reducing unemployment. Entrepreneurs must be brave in taking risks, good at taking advantage of opportunities, creative and innovative. Entrepreneurial interest in Indonesia is still very low. The number of entrepreneurs in Indonesia is only 0.18 percent of the total population, still far below other countries, namely Malaysia, which is 2 percent, America 4 percent, and Singapore 7 percent. This study aims to find problems faced by business actors to increase business independence through the development of a self-efficacy model. Self-efficacy or self-efficacy is a person's confidence to face problems. An entrepreneur must have the confidence to be able to manage his business. An effort will be successful if it is managed properly. Based on the pre-survey results, there are still many students who are not interested in becoming entrepreneurs because they lack confidence to manage their business.